2007
DOI: 10.1089/ars.2006.1513
|View full text |Cite
|
Sign up to set email alerts
|

Does Thioredoxin-1 Prevent Mitochondria- and Endoplasmic Reticulum-Mediated Neurotoxicity of 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine?

Abstract: We show that 1-methyl-4-phenylpyridinium ion (MPP(+)), an active metabolite of 1-methyl-4-phenyl-1,2,3,6- tetrahydropyridine (MPTP), induces cytotoxicity via endoplasmic reticulum (ER)- and mitochondria-mediated pathways, and thioredoxin-1 (TRX-1), a redox-active protein, prevents MPTP-induced neurotoxicity. TRX-1 overexpression suppressed reactive oxygen species and the ATP decline caused by MPP(+) in HepG2 cells. MPP(+) activated caspase-12 in PC12 cells and induced cytotoxicity in HeLa-rho(0) cells lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…The mechanism of Nrf2-mediated cytoprotection relies on the ability of Nrf2 target genes. Heme oxygenase-1 and thioredoxin, two important targets of Nrf2, play roles in modulating ER stress (38)(39)(40). These results suggest that SF prevents ER stress response by 6-OHDA through the activation of Nrf2.…”
Section: Discussionmentioning
confidence: 79%
“…The mechanism of Nrf2-mediated cytoprotection relies on the ability of Nrf2 target genes. Heme oxygenase-1 and thioredoxin, two important targets of Nrf2, play roles in modulating ER stress (38)(39)(40). These results suggest that SF prevents ER stress response by 6-OHDA through the activation of Nrf2.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to antioxidants, it has various biological activities, including the modulation of ER stress and inhibition of apoptosis [38,39]. Thioredoxin is also known as an endogenous inhibitor of ASK1, which mediates apoptosis on ER stress [40].…”
Section: Discussionmentioning
confidence: 99%
“…MPP + , the active metabolite of MPTP, causes mitochondrial stress and ER stress, leads to the production of superoxide radical and down-regulates the TRX-1 production (Bai et al, 2002(Bai et al, , 2007Itano et al, 1994;Nicklas et al, 1985). It has been reported that overexpression of TRX-1, administration of TRX-1, or an inducer of TRX-1 attenuates MPTP/MPP + -induced neurotoxicity (Bai et al, 2002(Bai et al, , 2007. In this study, we also found that PTS, an inducer of TRX-1, attenuated MPP + -induced neurotoxicity in vitro (Figs.…”
Section: Discussionmentioning
confidence: 99%